Examining The Influence of Trade Openness on the Economic Growth of Ghana - Aperegdina, Gerald Nsorlemna (Issues in Economics and Business, 2022)
Despite the prominence of trade liberalization or openness as an economic topic over last decades, the debate among economists and experts on the relationship between trade openness and economic growth is still open. This study purposed to examine, as the main objective, the impact of trade openness on economic growth in Ghana from 1990 to 2019. The study sought to investigate the relationship between trade openness and economic growth in Ghana. The study incorporated trade openness, investment, inflation, industrial value and labour force as the additional variables. In view of this, the Granger causality test was applied to ascertain the flow of information between time series which helped to make authentic forecasts of the data and model. To test for stationarity of the data, the augments Dickey-Fuller (ADF) (Dickey and Fuller, 1981) was applied. The findings of the evaluation suggest that trade openness has a negative impact on the Ghanaian economy and the degree of influence on Economic Growth is at a 1% level of significance and not statistically strong. This result is consistent with other studies including (Pickson et al, 2018; Kwegyir-Aggrey, 2019). Also, the study was aimed towards advocating some substantial policies for Ghana’s policymakers to help develop trade and economic growth.